2019
DOI: 10.1111/chd.12780
|View full text |Cite
|
Sign up to set email alerts
|

Lost in the system? Transfer to adult congenital heart disease care—Challenges and solutions

Abstract: Objective Transfer of congenital heart disease care from the pediatric to adult setting has been identified as a priority and is associated with better outcomes. Our objective is to determine what percentage of patients with congenital heart disease transferred to adult congenital cardiac care. Design A retrospective cohort study. Setting Referrals to a tertiary referral center for adult congenital heart disease patients from its pediatric referral base. Patients This resulted in 1514 patients age 16‐30, seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
2
16
2
1
Order By: Relevance
“…In particular, where patients appear stable and transfer is mandated by age 18, gaps in care are observed with > 50% of patients falling out of care from 12 to 18 years of age 42 and only 47% having at least 1 followup in an ACHD centre before age 22, with substantially worst transfer rates in the US. 59,60 Moreover, we have shown that only 20%-25% of ACHD patients receive follow-up care in ACHD centres in accordance with guideline recommendations. 57,61 Beyond considerations of ACHD expert centres' care needs, for the majority of an ACHD patient's life, the burden of health care management is largely carried by the patient and their family.…”
Section: Health Services Delivery: What Are the Needs?mentioning
confidence: 82%
“…In particular, where patients appear stable and transfer is mandated by age 18, gaps in care are observed with > 50% of patients falling out of care from 12 to 18 years of age 42 and only 47% having at least 1 followup in an ACHD centre before age 22, with substantially worst transfer rates in the US. 59,60 Moreover, we have shown that only 20%-25% of ACHD patients receive follow-up care in ACHD centres in accordance with guideline recommendations. 57,61 Beyond considerations of ACHD expert centres' care needs, for the majority of an ACHD patient's life, the burden of health care management is largely carried by the patient and their family.…”
Section: Health Services Delivery: What Are the Needs?mentioning
confidence: 82%
“…Im klinischen Alltag kommt es regelmäßig vor, dass sich Patienten in kardiologischen Praxen und Kliniken vorstellen, deren AHF bereits im Kindesalter diagnostiziert wurde, jedoch zu dieser Zeit keiner weiteren Therapie bedurfte. Aufgrund einer Versor-gungslücke ("lost to follow-up") befanden sich diese Patienten dann nicht selten über viele Jahre oder Jahrzehnte in keiner strukturierten und regelmäßigen Nachsorge und präsentieren sich mit relevanten Rest-und Folgeproblemen oder einer Leistungseinschränkung, was mit einer erhöhten Morbidität und Letalität einhergehen kann [2,8,9]. Demgegenüber gibt es auch Patienten, bei denen ein AHF erstmals im Erwachsenenalter diagnostiziert wurde.…”
Section: üBerraschende Echobefunde Als Erstdiagnose Eines Angeborenen Herzfehlers Im Erwachsenenalter Surprising Echo Findings As First Dunclassified
“…However, remaining in care is associated with improved long-term outcomes. 54 Anesthesiologists who encounter these patients should refer them back into ACHD specialty care.…”
Section: Adult Congenital Heart Diseasementioning
confidence: 99%